Critical digitality: from the virtual to the digital - Maldonado, Jorge Francisco; Rodríguez, Dairon Alfonso (Praxis Filosófica, 2017)
This paper argues that the idea of “virtual” or “virtuality” belongs to a theoretical perspective that intends to explain components of the phenomenon of technological society nowadays. Firstly, the digital perspective is explained in its ontological basic structure: binary codes that organize a physical set or hardware according to logical rules, therefore the idea of a network society, virtual communication and digital human beings are concepts that are not really grasping the problem of the digital technology in our society. A digital perspective assumes the need to understand digital technology in its physical functioning, which allows a complete picture of the problem and enables the subsequent critical analysis of the virtual perspective. Secondly, the virtual perspective is analyzed from the digital perspective to its main metaphysical assumptions: simulation, as a presupposed moral ideal; and functionality, as a presupposed instrumental ideal. Finally, the conclusion explains the possibilities given by the digital perspective in order to assume new challenges of the digital universe, in contrast to a virtual perspective which would pre-limit such possibilities to previous needs to be satisfied. Thus, this paper rather than showing a well-defined argument it urges a reorientation of our notions of the virtual and the digital.